The Influence of Advertising Exposure and Frequency of Parent-Children Communication towards Purchase Request Food and beverage Products from Children to Parent - Reni Yunita Muyaningsih; Nurist Surayya Ulfa S,Sos, M.Si (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Children are the potential market for the marketers because they are seen as a target in three markets, such as current market, future market and influential market. Therefore, marketers would seek for appropriate strategies to target children market. One of strategy that employed by marketers of food and beverage products in targeting children is advertising to persuade them by attractive ads. Because children have limited cognitive ability, they have to given socialization consumers by the parents so the children didn’t accept the information provided ads as a truth which will raise purchase request of children. The aims of this study to determine the influence of television advertising exposure and frequency of parent-children communication towards purchase request food and beverage products from children to parent. The theory that used was Advertising Exposure Processing Model and Children in Consumer Socializations. This type of research is explanatory research. The sample in this study are children aged 7 to 11 years who were exposed to food and beverage products on television. Respondents were taken from 50 respondents using non-random sampling technique. Data analysis used simple linear regression analysis with SPSS. The first hypothesis test results indicated that television advertising exposure (X1) isn’t significantly affect purchase request food and beverage products from children to parent (Y), while the significance of the results indicated the value of 0.231. The second hypothesis test indicated that frequency of parent-children communication (X2) significantly affects purchase request food and beverage products from children to parent (Y), with the results that indicates the value of 0.007.